2005
DOI: 10.1097/01.wnr.0000183904.15773.47
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation can regulate arterial blood pressure in awake humans

Abstract: The periaqueductal grey matter is known to play a role in cardiovascular control in animals. Cardiovascular responses to electrical stimulation of the periventricular/periaqueductal grey matter were measured in 15 awake human study participants following implantation of deep brain stimulating electrodes for treatment of chronic pain. We found that stimulation of the ventral periventricular/periaqueductal grey matter caused a mean reduction in systolic blood pressure of 14.2+/-3.6 mmHg in seven patients and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 25 publications
(29 reference statements)
9
82
1
3
Order By: Relevance
“…Human DBS and animal studies have identified that dlPAG activation triggers active coping strategies, involving sympathoexcitation, hyperventilation and short‐duration, non‐opioid‐mediated analgesia [Bandler et al, 2000; Green et al, 2005; Keay and Bandler, 2001; Pereira et al, 2010]. Our results are consistent with these observations.…”
Section: Discussionsupporting
confidence: 91%
“…Human DBS and animal studies have identified that dlPAG activation triggers active coping strategies, involving sympathoexcitation, hyperventilation and short‐duration, non‐opioid‐mediated analgesia [Bandler et al, 2000; Green et al, 2005; Keay and Bandler, 2001; Pereira et al, 2010]. Our results are consistent with these observations.…”
Section: Discussionsupporting
confidence: 91%
“…Its autonomic effects have been well studied in animals [92,[114][115][116][117] and changes noted with DBS [101]. We have demonstrated a positive correlation between the degree of analgesia in patients receiving PAG DBS and the magnitude of blood pressure reduction [118], and have shown that whereas dorsal PAG stimulation can acutely elevate blood pressure, ventral stimulation reduces it [119,120]. Such findings advance investigations for objective markers of chronic pain and also the potential selection of patients who may respond best to PAG DBS.…”
Section: Physiologysupporting
confidence: 53%
“…The advancement of neuroimaging techniques has provided an opportunity for translation of these findings to humans and the insular and anterior cingulate cortices have been suggested as human brain regions that are activated by central command during exercise (45,168,234,235,339,379,380). More recently, direct electrical stimulation of midbrain areas during neurosurgery (e.g., deep brain stimulation) in awake humans has been used to enhance our understanding of potential central command areas (16,117,118,338) (Fig. 7).…”
Section: Neural Cardiovascular Control Mechanisms Central Commandmentioning
confidence: 97%